Science in the Representation of Young Students from São Luís – MA (Research, Society and Development, 2023)
The present work deals with the representation that some young students from São Luís (MA) have regarding Science. This work is justified because an alarming wave of scientific negationism has emerged in Brazil, contrary to what was expected: that Science had a secure and prominent place in society, with enough authority to indicate the best solutions to a variety of problems. If before science was overrated, taken as absolute and as the owner of the truth, it started to be delegitimized and devalued by group speculations and by personal opinions without any foundations, in a complete disservice to progress, opening a field for conspiracy and fundamentalist discourses and lowering the demand for study and improvement, both increasingly necessary in a world governed by scientific and technological specialization. Without sticking to one or another conception of science and the scientific work, we tried to verify the conceptions of this public, through dialogues and the application of a questionnaire, about science, its usefulness, modus operandi, and their identifications with the scientific work. Fifty-nine students between 15 and 18 years old from public (36.1%) and private (63.9%) schools participated. The results indicated that the majority (90%) understood that science is a social activity performed in various spaces and institutions, which is characterized by having articulated knowledge, obtained methodically, able to understand and predict phenomena (66.7%) and that it is a knowledge like any other, subject to errors of interpretation and measurement, but that it is obtained through methods (81.7%).